A forgotten contribution Melanchthon’s catechisms in the service of the 16th-century Reformation - Oseka, Mateusz (2016)
The present article examines Melanchthon’s catechisms in their historical setting and explores their theological potential, especially in terms of the Protestant concept of vocation by virtue of which theology of the 16th-century Reformation was able to give new meaning to the treadmill of daily life and to the entire tangible existence of human beings. Through his mature catechism (Catechesis puerilis) Melanchthon vindicated the mundane life as the ultimate endeavour of human beings, while the Reformation affirmation of the tangible left a lasting impression upon mainstream Protestantism and it has been acclaimed by both conservative and progressive theologians.